CNVs affecting cancer predisposing genes (CPGs) detected as incidental findings in routine germline diagnostic chromosomal microarray (CMA) testing. Issue 2 (16th September 2017) - Innes, Josie; Reali, Lisa; Clayton-Smith, Jill; Hall, Georgina; Lim, Derek HK; Burghel, George J; French, Kim; Khan, Unzela; Walker, Daniel; Lalloo, Fiona; Evans, D Gareth R; McMullan, Dominic; et al.
Abstract : Background: Identification of CNVs through chromosomal microarray (CMA) testing is the first-line investigation in individuals with learning difficulties/congenital abnormalities. Although recognised that CMA testing may identify CNVs encompassing a cancer predisposition gene (CPG), limited information is available on the frequency and nature of such results. Methods: We investigated CNV gains and losses affecting 39 CPGs in 3366 pilot index case individuals undergoing CMA testing, and then studied an extended cohort (n=10 454) for CNV losses at 105 CPGs and CNV gains at 9 proto-oncogenes implicated in inherited cancer susceptibility. Results: In the pilot cohort, 31/3366 (0.92%) individuals had a CNV involving one or more of 16/39 CPGs. 30/31 CNVs involved a tumour suppressor gene (TSG), and 1/30 a proto-oncogene (gain of MET ). BMPR1A, TSC2 and TMEM127 were affected in multiple cases. In the second stage analysis, 49/10 454 (0.47%) individuals in the extended cohort had 50 CNVs involving 24/105 CPGs. 43/50 CNVs involved a TSG and 7/50 a proto-oncogene (4 gains, 3 deletions). The most frequently involved genes, FLCN (n=10) and SDHA (n=7), map to the Smith-Magenis and cri-du-chat regions, respectively. Conclusion: Incidental identification of a CNV involving a CPG is not rare and poses challenges for future cancer risk estimation. Prospective data collection from CPG-CNV cohorts ascertained incidentally and through syndromic presentations is required to determine the risks posed by specific CNVs. In particular, ascertainment and investigation of adults with CPG-CNVs and adults with learning disability and cancer, could provide important information to guide clinical management and surveillance.